Evaluation Development and Use in Social Work Practice - Derrick W. Gervin; Sarita K. Davis; Jenny L. Jones; Margaret S.E. Counts-Spriggs; Kimberly D. Farris (The Evaluation Center at Western Michigan University, 2010)
Background: Social workers entering the profession typically receive little, if any, content or training on evaluation practice. This is, in part, due to limited course offerings outside of the typical courses in most schools of social work. In addition, practicing social workers who often serve in the role as field instructors have not fully embraced the use of research in practice, and tend to employ less rigorous evaluative methods. Purpose: The purpose of this study was to explore the development and use of evaluation knowledge among social work practitioners who supervise social work students. Setting: Not applicable. Intervention: Not applicable. Research Design: A mixed method, sequential research design within the context of an exploratory study was used to determine factors that facilitate evaluation, identify and prioritize evaluation competencies, and determine the extent to which evaluation constructs contribute to self efficacy, evaluation competency, evaluation influence, and leadership behaviors. Data Collection and Analysis: A web-based survey was used followed by a participatory method that included the use of a web-based software to identify and prioritize activities that contribute to the development of evaluation knowledge and skill. Findings: Results suggest social work education has a critical role in promoting evaluation practice, establishing evaluation practice competencies, and using evaluation results to inform policy and practice.